K-Nearest Neighbor Grouping in Excess of Semantically Secure Encryption Interactive Evidence - Maniraj, V; Krishnaveni, V (International Journal of Computer Sciences and Engineering, 2025)
Data Mining has wide use in numerous fields such as financial, medication, medical research also, among govt. departments. Grouping is one of the widely connected works in Data Mining applications. For the past several years, due to the increment of diverse security problems, numerous conceptual also, practical options to the grouping issue have been proposed under diverse security designs. On the other hand, with the latest reputation of cloud processing, users now have to be capable to delegate their data, in encoded form, as well as the Data Mining undertaking to the cloud. Considering that the information on the cloud is in secured type, current privacy-ensuring grouping strategies are not appropriate. In this paper, we concentrate on fixing the grouping issue over encoded data. In specific, we prescribe a secured k-NN classifier over secured information in the cloud. The proposed convention safeguards the security of information, solace of user’s criticism query, also, disguises the information access styles. To the best of our information, our undertaking is the initially to make a secured k-NN classifier over secured information under the semi-honest model. Also, we empirically evaluate the execution of our proposed convention utilizing a real-world dataset under diverse parameter configurations.